2017
DOI: 10.1007/s10336-017-1462-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of anthropogenic material affects bird nest arthropod community structure: influence of urbanisation, and consequences for ectoparasites and fledging success

Abstract: Nests are a critically important factor in determining the breeding success of many species of birds. Nevertheless, we have surprisingly little understanding of how the local environment helps determine the materials used in nest construction, how this differs among related species using similar nest sites, or if materials used directly or indirectly influence the numbers of offspring successfully reared. We also have little understanding of any potential links between nest construction and the assemblage of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 63 publications
(96 reference statements)
2
40
0
1
Order By: Relevance
“…The positive associations in this case could be related with the use of the same food source, nestlings, but the negative relationship with blackflies is difficult to explain. However, some studies have shown that arthropod abundance inside nests can affect negatively flea abundance (Heeb et al 2000, Hanmer et al 2017. We also find a negative relationship between final abundance of blowflies and the final abundance of mites in nests.…”
Section: Discussionsupporting
confidence: 54%
“…The positive associations in this case could be related with the use of the same food source, nestlings, but the negative relationship with blackflies is difficult to explain. However, some studies have shown that arthropod abundance inside nests can affect negatively flea abundance (Heeb et al 2000, Hanmer et al 2017. We also find a negative relationship between final abundance of blowflies and the final abundance of mites in nests.…”
Section: Discussionsupporting
confidence: 54%
“…On the one hand, several authors found no variation in nest mass or size along an urbanisation gradient for Blue or Great Tits in different European cities (Glądalski et al 2016;Reynolds et al 2016;Lambrechts et al 2017). On the other hand, Hanmer et al (2017) found that Blue Tits, but not Great Tits, in the same English town had lighter nests in more urbanised areas. This could be explained in a thermal context, as several studies have found geographical variation in nest size/mass that has been attributed to variations in ambient temperature (Deeming et al 2012;Mainwaring et al 2012Mainwaring et al , 2014aBiddle et al 2016).…”
Section: Nest Design and Urbanisationmentioning
confidence: 87%
“…The use of cigarette butts is not just restricted to House Finches in Mexico (Suárez-Rodríguez and Macías Garcia 2017), and has been found in other species such as House Sparrows in North America (Suárez-Rodríguez et al 2013 and Asia (Radhamany et al 2016), suggesting that it might be a general behavioural innovation for urban-adapted species. In contrast, Blue Tits (Cyanistes caeruleus), a species that does not use cigarette butts as nest constituents, in the town of Reading, UK using more anthropogenic nesting material had larger numbers of fleas (Siphonaptera) within their nest contents (Hanmer et al 2017). The authors argue that this is caused by a reduction in the diversity of nest-dwelling arthropods (including potential competitors and predators of flea larvae).…”
Section: Nest Design and Urbanisationmentioning
confidence: 99%
See 2 more Smart Citations